(untitled) (Research, Society and Development, 2020)
The objective of this study was to verify if the school environment and Physical Education classes modify the motor performance of children from public schools (EPb) and private schools (EPa) of basic education in a city in the south of Minas Gerais. The study involved the participation of 100 children, of both sexes, aged between six and nine years, from two educational institutions, one private and the other public. The school environment and children were assessed punctually, using three instruments: a) test to assess fundamental motor skills (TGMD-2); b) protocol of observations of physical education classes to assess their quality; c) checklist to assess the infrastructure, material resources and content worked on by the teacher. For data analysis, the “two-way ANOVA” with independent variables and the “ANCOVA” covariance test were used and the results showed that EPa students had better motor proficiency when compared to EPb. The analysis of covariance showed that the school environment is related to the process of developing fundamental motor skills, however, the teacher’s pedagogical practice did not significantly interfere in the children’s learning.